2016
DOI: 10.1093/infdis/jiw561
|View full text |Cite
|
Sign up to set email alerts
|

Inflammasome activation underlies central nervous system deterioration in HIV-associated tuberculosis

Abstract: Tuberculous meningitis (TBM) is a frequent cause of meningitis in individuals with human immunodeficiency virus (HIV) infection, resulting in death in approximately 40% of affected patients. A severe complication of antiretroviral therapy (ART) in these patients is neurological tuberculosis–immune reconstitution inflammatory syndrome (IRIS), but its underlying cause remains poorly understood. To investigate the pathogenesis of TBM-IRIS, we performed longitudinal whole-blood microarray analysis of HIV-infected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(69 citation statements)
references
References 30 publications
3
66
0
Order By: Relevance
“…The gene transcripts that were most abundant in patients with IRIS versus non-IRIS controls, and clearly discriminatory on a PCA plot, were S100A9, IL-10, NLRP12, and COX-1. Increased expression of inflammasome and neutrophilassociated genes in TB-IRIS is consistent with previous results, 12,31 but the lower abundance of TCR-associated genes in patients with TB-IRIS was unexpected and deserves further analysis. This may reflect poor reconstitution of normal T-cell function in TB-IRIS and again supports the concept that the phenomenon is driven by innate inflammation without an orchestrated acquired immune response.…”
Section: Ln Granulomas From Patients With Iris Show Significant Neutrsupporting
confidence: 89%
“…The gene transcripts that were most abundant in patients with IRIS versus non-IRIS controls, and clearly discriminatory on a PCA plot, were S100A9, IL-10, NLRP12, and COX-1. Increased expression of inflammasome and neutrophilassociated genes in TB-IRIS is consistent with previous results, 12,31 but the lower abundance of TCR-associated genes in patients with TB-IRIS was unexpected and deserves further analysis. This may reflect poor reconstitution of normal T-cell function in TB-IRIS and again supports the concept that the phenomenon is driven by innate inflammation without an orchestrated acquired immune response.…”
Section: Ln Granulomas From Patients With Iris Show Significant Neutrsupporting
confidence: 89%
“…have also demonstrated that neutrophil abundant transcripts were significantly higher in those who develop IRIS from before ART initiation until the onset of TBM‐IRIS . After initiation of ART a significantly higher number of transcripts associated with canonic and noncanonic inflammasome activation were found in patients who went on to develop IRIS than in those who did not . These observations together with the finding that inflammasome activation can contribute to pyroptosis suggest that tissue injury observed in TBM may be partly induced by inflammasome‐mediated pyroptosis.…”
Section: Differences In the Intracerebral Immune Response In The Hiv‐mentioning
confidence: 78%
“…Using longitudinal microarray analysis of blood from patients with HIV and TBM Marais et al. have also demonstrated that neutrophil abundant transcripts were significantly higher in those who develop IRIS from before ART initiation until the onset of TBM‐IRIS . After initiation of ART a significantly higher number of transcripts associated with canonic and noncanonic inflammasome activation were found in patients who went on to develop IRIS than in those who did not .…”
Section: Differences In the Intracerebral Immune Response In The Hiv‐mentioning
confidence: 97%
“…It was concluded that MPO may be involved in the oxidative stress associated with BM, as well as potentially contributing to BBB disruption. Marais et al (2016) indicated a significant increase in neutrophil-dependent inflammatory response biomarkers, including MPO, in adult TBM and HIV co-infection patients with paradoxical immune reconstitution inflammatory syndrome. Lastly, Üllen et al (2013) indicated that BBB dysfunction associated with neuroinflammation caused by MPO can be partially reversed by using para-aminobenzoic acid (PABA) hydrazide, first shown by Forghani et al (2012) to effectively treat multiple sclerosis in mice.…”
Section: Myeloperoxidasementioning
confidence: 97%